Recognition and Global Politics - Schick, Kate; Hayden, Patrick (Manchester University Press, 2016)
"The notion of recognition, drawing on the philosophy of Hegel, has become increasingly central to international debates in recent years, yet there have been few attempts to critically examine new theoretical positions and empirical analyses of its possible meanings, limits and manifestations. Recognition and global politics examines the potential and limitations of the discourse of recognition as a strategy for reframing justice and injustice within contemporary world affairs. Drawing on resources from social and political theory and international relations theory as well as other areas including feminist theory, postcolonial studies and social psychology, this ambitious collection explores a range of political struggles, social movements and sites of opposition that have shaped certain practices and informed contentious debates in the language of recognition. How have recognition-based claims been deployed in relation to international, transnational and global politics? The contributors speak to central issues in current debates about cosmopolitanism, genocide, human rights, global capitalism, multiculturalism, rebellion and the environment. This innovative volume will push the boundaries of the debate on recognition into new areas, opening up provocative lines of inquiry and critique."